2020
DOI: 10.3390/ma13122772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Treatment on Ceria-Stabilized Zirconia/Alumina Nanocomposite (NANOZR)

Abstract: Nanostructured zirconia/alumina composite (NANOZR) has been explored as a suitable material for fabricating implants for patients with metal allergy. In this study, we examined the effect of UV treatment on the NANOZR surface. The experimental group was UV-treated NANOZR and the control group was untreated NANOZR. Observation of the surface of the UV-treated materials revealed no mechanical or structural change; however, the carbon content on the material surface was reduced, and the material surface displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Ujino et al demonstrated that the in vitro and in vivo atmospheric-pressure plasma treatment of titanium surfaces was effective in improving the adhesion ability of RBMCs and inducing hard tissue differentiation [ 31 ]. Further, atmospheric-pressure plasma treatment of the zirconia material surface was found to be as effective as titanium in improving bone conduction performance, as reported in our previous studies [ 33 , 34 ]. Several studies have revealed that rendering the material surface superhydrophilic decreases the carbon and oxidative stress, thus affecting the behavior of RBMCs [ 29 , 35 ].…”
Section: Introductionsupporting
confidence: 80%
“…Ujino et al demonstrated that the in vitro and in vivo atmospheric-pressure plasma treatment of titanium surfaces was effective in improving the adhesion ability of RBMCs and inducing hard tissue differentiation [ 31 ]. Further, atmospheric-pressure plasma treatment of the zirconia material surface was found to be as effective as titanium in improving bone conduction performance, as reported in our previous studies [ 33 , 34 ]. Several studies have revealed that rendering the material surface superhydrophilic decreases the carbon and oxidative stress, thus affecting the behavior of RBMCs [ 29 , 35 ].…”
Section: Introductionsupporting
confidence: 80%
“…UV light treatment of zirconia may improve surface bioactivity via “biological activation” [ 99 ]. UV treatment reduced cytotoxicity [ 100 ], enhanced protein adsorption, cell proliferation, adhesion and differentiation [ [101] , [102] , [103] ] and inhibited oxidative stress (reactive oxygen species production) and inflammatory responses [ 104 ]. UV treatment requires simple equipment and procedure, is easy to implement, has a low cost and is not restricted by type of abutment material, including titanium, zirconia and polyether ether ketone (PEEK) [ [100] , [101] , [102] , [103] , 105 , 106 ].…”
Section: Surface Modification Of Zirconia Abutmentsmentioning
confidence: 99%
“…Enhancement in the strength and generation of the surface compressive induced stress resulted from the transformation over the surface of ground specimens. Komasa et al [ 149 ] assessed the impact of UV treatment on the CSZ/A NCs. Surface evaluation studies declared no structural or mechanical changes, but a decrease in the carbon content of the surface was observed.…”
Section: Stabilization Mechanism Of Zr‐nss: Exploring the Role Of Doping Agentsmentioning
confidence: 99%
“…It was also claimed that the UV‐C irradiation significantly altered the aesthetic in color and enriched the MC3T3‐E1 cell adhesion on ZrO 2 by photofunctionalization. Recently, Komasa et al [ 149 ] estimated the effect of UV treatment on CSZ/A nanostructured composite and revealed that the UV irradiation does not alter the mechanical or structural properties but reduces the carbon content of the surface material. Such a UV‐irradiated material exhibited advanced superhydrophilicity.…”
Section: Optimized Approaches For Improving Surface Properties Of Zr‐nssmentioning
confidence: 99%